Google Patents versus Lens: scientific literature citations in patents - Velayos Ortega, Gema; López Carreño, Rosana (Revista General de Información y Documentación, 2021)
A comparison of open patent search engines (Google Patents and Lens) is carried out to analyse the visibility and treatment of patent scientific literature citations. Among the results, the linkage of these citations with other sources of scientific-academic information, the lack of standardization of bibliographic records or the incorporation of data analysis tools such as citation networks or influence maps stand out. The study determines that the treatment of these references is becoming more and more important in these patent information platforms that provide novel solutions to the treatment of Non-Patent Literature (NPL), promoting the interconnection of citations of scientific publications in patents. The assessment of the technological impact of these citations, in line with the traditional scientific impact, will require the establishment of new scientometric indicators for their evaluation.